2021
DOI: 10.1155/2021/9958081
|View full text |Cite
|
Sign up to set email alerts
|

High Neutrophil‐to‐Lymphocyte Ratio and Platelet‐to‐Lymphocyte Ratio Are Associated with Poor Survival in Patients with Hemodialysis

Abstract: Background. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers for systemic inflammation condition. Although NLR has emerged as a risk factor for poor survival in end-stage renal disease (ESRD) patients, the relationship between PLR and mortality is still unknown. We aimed to explore the interaction of NLR and PLR in predicting mortality in hemodialysis (HD) patients. Method. We enrolled 360 HD patients for a 71-month follow-up. The endpoint was all-cause and cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Generally, hemodialysis patients are characterized by uremia-related immunological abnormalities, such as decreased general blood counts and malfunction of immune cells [ 40 ]. Blood morphology-derived parameters obtained from five-part differential blood count were shown to be altered in various inflammatory states, including COVID-19 [ 41 ], which was also observed for CKD COVID-19 patients [ 42 , 43 , 44 ]. Renal dysfunction is associated with an increase in endothelial injury-related BNP and NT-pro-BNP markers that were found to be associated with disease severity and mortality in COVID-19 patients [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…Generally, hemodialysis patients are characterized by uremia-related immunological abnormalities, such as decreased general blood counts and malfunction of immune cells [ 40 ]. Blood morphology-derived parameters obtained from five-part differential blood count were shown to be altered in various inflammatory states, including COVID-19 [ 41 ], which was also observed for CKD COVID-19 patients [ 42 , 43 , 44 ]. Renal dysfunction is associated with an increase in endothelial injury-related BNP and NT-pro-BNP markers that were found to be associated with disease severity and mortality in COVID-19 patients [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…The establishment of the predictive role of the biomarkers for both the progression of CKD and the negative outcome is an intensely discussed topic in recent years’ literature. High NLR and PLR values have been associated with the evolution of CKD towards ESKD and with a high mortality rate in numerous studies [ 29 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the article published by Zhang et al showed the association of high NLR values with all causes of mortality. In contrast, high PLR values are a predictive factor for cardiovascular mortality [ 44 ]. In the paper published by Xiang et al, which included 355 patients on dialysis for at least 6 months, high MLR values were found to be independent factors of adverse prognosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin fragment analyses, thrombin-antithrombin III complex, and d-dimer evaluation can assess the "pre-clotting" stages, as well as platelet-to-lymphocyte ratio, obtained by dividing the absolute platelet count by the absolute lymphocyte count, which could represent a novel marker of inflammation in HD patients [30][31][32].…”
Section: Platelets and Coagulation Systemmentioning
confidence: 99%